Peran Lembaga Dalam Memberdayakan Masyarakat Berbasis Pengembangan Sumber Daya Alam - Hamdan Maulana; Dadang Kuswana; Dedi Herdiana (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
This study aims to analyze the role of LMDH in improving public welfare through natural tourism to determine the norms established by LMDH, find out the forms of public participation, and the results of LMDH empowerment in improving welfare through natural tourism. This research is qualitative research using the descriptive method. The techniques used in this research are observation, interview, and documentation techniques. Data analysis was carried out by reducing data and interpreting logic connected to the context of public empowerment. The results showed that public empowerment, which has been done by LMDH through natural tourism, was strengthening human resources and developing natural resources. The strengthening of human resources with the provision of administrative materials, technical materials, and motivation to have skills and natural resource development. The empowerment results include the emergence of awareness to develop existing potential, increase public income, open business opportunities, and carry out social activities well.